Surgical and visual outcomes of posterior dislocated lens fragments after cataract surgery during 5-years at a tertiary eye hospital of North India - Paul, Lagan; Agarwal, Manisha; Singh, Shalini; Mayor, Rahul; Gupta, Chanda; Gujral, Gaganjeet Singh (Nepalese Journal of Ophthalmology, 2019)
Objective: To determine the surgical and visual outcomes of posteriorly dislocated lens fragments in the vitreous cavity in patients undergoing cataract surgery. Methods: A total of 149 eyes of 149 patients from 2013 to 2018 were included in the study. The primary cataract surgery was performed either at the base hospital and its peripheral centres or referred from elsewhere. Pars plana vasectomy and nucleus removal was performed along with implantation of intraocular lens, wherever possible. Success was defined as best corrected visual acuity (BCVA) ≥ 6/12 at 3 months follow up. Poor visual outcome was defined as per WHO guidelines as BCVA ≤ 3/60. Results: Posterior capsular rupture and dislocation into vitreous cavity most frequently occurred during phaco-fragmentation in cases of phacoemulsification and during nucleus delivery in cases of small incision cataract surgery. Early vitrectomy was performed within 3 days in 36.2% of cases and within 14 days in 63.8% of cases. Successful visual outcome was achieved in 85.2% of patients at 3 months follow up after vitrectomy. Iatrogenic retinal break occurred in five patients during vitrectomyand five patients had retinal detachment. Poor visual outcome was observed in 12eyes, out of which glaucomatous optic neuropathy seen in 5 cases, cystoid or diabeticmacular edema in 4 cases and age related macular degeneration in 3 cases. Conclusion: Posterior dislocation of lens can be successfully managed in majority of cases with vitreoretinal surgical intervention. The timing of vitrectomy whether performed early or late did not affect the visual outcome. The most important predictorof final visual acuity after PPV for retained lens fragments is a less complicated clinical course without any associated complications such as retinal detachment, cystoidmacula edema and glaucoma. Expertise of the primary cataract surgeon could not be assessed in this study, though surgeon grade with more experience is an important factor in the assessment of complications during the cataract surgery.